The Adoption of Data Journalism Practices in Ghanaian Newsrooms: Exploring the Perspectives of Media Stakeholders - Etrue, M. (University of Ghana, 2024)
This study investigates the adoption of data journalism in Ghana, analysing the practices, perceptions, and challenges faced by key stakeholders within the media industry. Grounded in Diffusion of Innovation theory, the research explores how journalists, newsroom managers, civic technology groups, training organizations, and government agencies engage with data journalism, an emerging field in the country's media landscape. Through in-depth qualitative interviews with 17 participants, the study reveals both the potential and limitations of data journalism in Ghana. Findings show that while data journalism is recognised for its capacity to enhance reporting depth and accuracy, its integration into newsrooms is impeded by several factors: a lack of readily accessible data, limited financial resources, and the slow acquisition of technical skills among journalists. Despite these challenges, early adopters within Ghana’s media sector, particularly in investigative reporting and election coverage, are showcasing the value of data-driven storytelling. The study also highlights the importance of cross-disciplinary collaboration and government efforts in fostering a culture of data sharing and data storytelling, although widespread adoption remains slow due to the perceived complexity of data journalism tools and practices.
MPhil. Communication Studies
Keywords: Data Journalism; Media Innovation; Diffusion of Innovation Theory; Ghanaian Media